Isolating High Antimicrobial Ability Lignin From Bamboo Kraft Lignin by Organosolv Fractionation - Yun, Jinyan; Wei, Liao; Li, Wei; Gong, Duqiang; Qin, Hongyu; Feng, Xiujing; Li, Guojiang; Ling, Zhe; Wang, Peng; Yin, Baishuang (Frontiers in Bioengineering and Biotechnology, 2021)
Lignin from different biomasses possess biological antioxidation and antimicrobial activities, which depend on the number of functional groups and the molecular weight of lignin. In this work, organosolv fractionation was carried out to prepare the lignin fraction with a suitable structure to tailor excellent biological activities. Gel permeation chromatography (GPC) analysis showed that decreased molecular weight lignin fractions were obtained by sequentially organosolv fractionation with anhydrous acetone, 50% acetone and 37.5% hexanes. Nuclear magnetic resonance (NMR) results indicated that the lignin fractions with lower molecular weight had fewer substructures and a higher phenolic hydroxyl content, which was positively correlated with their antioxidation ability. Both of the original lignin and fractionated lignins possessed the ability to inhibit the growth of Gram-negative bacteria (Escherichia coli and Salmonella) and Gram-positive bacteria (Streptococcus and Staphylococcus aureus) by destroying the cell wall of bacteria in vitro, in which the lignin fraction with the lowest molecular weight and highest phenolic hydroxyl content (L3) showed the best performance. Besides, the L3 lignin showed the ability to ameliorate Escherichia coli-induced diarrhea damages of mice to improve the formation of intestinal contents in vivo. These results imply that a lignin fraction with a tailored structure from bamboo lignin can be used as a novel antimicrobial agent in the biomedical field.